2013
DOI: 10.1111/clr.12302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of titanium brush on machined and sand‐blasted/acid‐etched titanium disc using confocal microscopy and contact profilometry

Abstract: This study showed that the treatment with the titanium brush did not significantly change the roughness parameters, including Sa and Sz, in both MA and SA surfaces. Correlations between confocal microscopy and surface profilometry showed high correlation with a Pearson correlation coefficient of 0.98.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 33 publications
4
33
1
Order By: Relevance
“…This study evaluating the adjunctive effect of a titanium brush in the decontamination of the implant surface during regenerative peri‐implantitis interventions has demonstrated a significant effect at 12 months post‐operatively in the main outcome variable (PPD reduction) with significant differences when compared with the standard intra‐surgical surface decontamination protocol using ultrasonic teflon tips and irrigation with 3% H 2 O 2 . This positive effect of the titanium brush has already been demonstrated in in vitro studies (John et al., ; Park et al., ) and in experimental studies (Carral et al., ). In this dog study, four surface decontamination protocols were compared during the surgical treatment of experimental peri‐implantitis (group 1, Tibrush® + CHX + H 2 O 2 ; group 2, Tibrush® + CHX; group 3, ultrasonic scalers + CHX; and group 4, control group, no treatment).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This study evaluating the adjunctive effect of a titanium brush in the decontamination of the implant surface during regenerative peri‐implantitis interventions has demonstrated a significant effect at 12 months post‐operatively in the main outcome variable (PPD reduction) with significant differences when compared with the standard intra‐surgical surface decontamination protocol using ultrasonic teflon tips and irrigation with 3% H 2 O 2 . This positive effect of the titanium brush has already been demonstrated in in vitro studies (John et al., ; Park et al., ) and in experimental studies (Carral et al., ). In this dog study, four surface decontamination protocols were compared during the surgical treatment of experimental peri‐implantitis (group 1, Tibrush® + CHX + H 2 O 2 ; group 2, Tibrush® + CHX; group 3, ultrasonic scalers + CHX; and group 4, control group, no treatment).…”
Section: Discussionsupporting
confidence: 53%
“…A new titanium brush made of titanium bristles with a stainless steel shaft has been recently commercialized for the open debridement of titanium surfaces during the surgical treatment of peri‐implantitis. In vitro investigations with the use of confocal laser microscopy and contact profilometry have shown that these titanium brushes did not significantly alter the microsurface topography of both machined and SLA implants (Park, Jeon, & Ko, ). Furthermore, improved plaque removal was observed when compared with steel curettes (John, Becker, & Schwarz, ).”…”
Section: Introductionmentioning
confidence: 99%
“…It has been claimed that a slowly rotating Ti brush is safe for use on implant surfaces, 174 and effective in removing biofilm compared to metal scalers, 172, 175 but these studies did not test different surface types nor did they use a complex biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Park et al in 2015 showed that a Ti brush used at 300 rpm for 40 seconds did not significantly affect Sa or Sz values, but did scratch SLA surfaces, as could be seen when the treated areas were examined by SEM. 174 Ti brushes appear to be more effective in removing biofilm than hand stainless steel curettes. 175 They can also be combined with other methods.…”
Section: Titanium Brushesmentioning
confidence: 95%
See 1 more Smart Citation